Utility of the Zebrafish Model for Studying Neuronal and Behavioral Disturbances Induced by Embryonic Exposure to Alcohol, Nicotine, and Cannabis - Collier, Adam D.; Abdulai, Abdul R.; Leibowitz, Sarah F. (Cells (Basel, Switzerland), 2023)
It is estimated that 5% of pregnant women consume drugs of abuse during pregnancy. Clinical research suggests that intake of drugs during pregnancy, such as alcohol, nicotine and cannabis, disturbs the development of neuronal systems in the offspring, in association with behavioral disturbances early in life and an increased risk of developing drug use disorders. After briefly summarizing evidence in rodents, this review focuses on the zebrafish model and its inherent advantages for studying the effects of embryonic exposure to drugs of abuse on behavioral and neuronal development, with an emphasis on neuropeptides known to promote drug-related behaviors. In addition to stimulating the expression and density of peptide neurons, as in rodents, zebrafish studies demonstrate that embryonic drug exposure has marked effects on the migration, morphology, projections, anatomical location, and peptide co-expression of these neurons. We also describe studies using advanced methodologies that can be applied in vivo in zebrafish: first, to demonstrate a causal relationship between the drug-induced neuronal and behavioral disturbances and second, to discover underlying molecular mechanisms that mediate these effects. The zebrafish model has great potential for providing important information regarding the development of novel and efficacious therapies for ameliorating the effects of early drug exposure.